Kiekybinės kaitos ir jų ikoninė funkcija - Akelaitienė, Gražina (Kalbotyra, 1995)
The article deals with non-automatic quantitative vowel changes which take place in word-formation. They are implicated by a derivational formant. In Lithuanian word formation the vowel quantity typically changes in the direction of increasing duration and intensity (V → V̄) and not the reverse. The functioning morphemes in word-formation are , , as well as , , the latter being less frequent. The long alternant has an informative function: it correlates with corresponding formants and derivational meanings. Quantitative alternations are especially regular in the derivatives of inflection -is, which have the meaning of substantivized actions, e.g., mū̃šis, stȳgis, bū̃vis.The quantity of root vowel can sometimes fulfill an iconic function. In some derivational oppositions, vowel lengthening ar shortening has a direct reference to the verb semantics (it symbolizes more/less intensive and long action) e.g., kìšti → kýšoti, trȳpti → tripinė́ti. Such alternation takes place in derivatives with modifying meanings.